The correlation between apraxia and neglect in the right hemisphere: A voxel-based lesion-symptom mapping study in 138 acute stroke patients. (November 2020) - Dressing, Andrea; Martin, Markus; Beume, Lena-Alexandra; Kuemmerer, Dorothee; Urbach, Horst; Kaller, Christoph P.; Weiller, Cornelius; Rijntjes, Michel
Abstract: Apraxia is frequently described after left hemisphere stroke and results from lesions to a complex network for motor cognition with dorso-dorsal, ventro-dorsal and ventral processing streams. Apraxia also occurs after right hemisphere stroke, but lesion correlates and underlying mechanisms remain to be elucidated. To clarify the role of the right hemisphere in apraxic deficits and the influence of neglect, we prospectively examined apraxia (imitation of meaningless postures and pantomime of tool use) and neglect in 138 acute right hemisphere stroke patients with first-ever ischemic stroke in the middle cerebral artery territory and identified corresponding lesion correlates using voxel-based lesion-symptom mapping. Imitation of meaningless postures was impaired as frequently as after left hemisphere stroke (38.4%) and was significantly associated with neglect. Imitation of meaningless postures was related to temporal (middle temporal gyrus, temporoparietal junction, superior temporal gyrus and sulcus), parietal (angular gyrus, parieto-occpitpial sulcus), secondary sensorimotor cortex and (peri-)insular lesions. Presence of neglect dichotomized the results: a lesion correlate for isolated imitation without neglect was found in the right parieto-occipital cortex, while imitation deficits, when co-occurring with neglect, were related to lateral occipito-temporal, superior temporal sulcus and (peri-)insular lesions. Pantomime of tool use deficits, typical for apraxia after left hemisphere lesions, were found in only 5 cases (3.6%) and only in the context of neglect, and were associated with occipital lobe, ventral and anterior temporal lobe, and inferior frontal (areas 45/47) lesions. The syndrome of apraxia after right hemisphere stroke differs from apraxia after left hemisphere stroke. Imitation deficits are found in both hemispheres after dorso-dorsal stream lesions. Neglect also leads to and explains deficits in imitation and pantomime in patients with right ventral stream lesions. Therefore, in right hemisphere lesions, apraxia can either be explained as impaired visuomotor transformation or as a result of visuospatial deficits.